PPN ATAS PENYERAHAN BATU BARA DALAM UNDANG-UNDANG CIPTA KERJA (MENAKAR POTENSI KENAIKAN ATAU PENURUNANNYA TERHADAP PENERIMAAN NEGARA) - Nabila Adriyani Putri; Imam Muhasan (Politeknik Keuangan Negara STAN, 2021)
With the enactment of Law Number 11 of 2020 on Job Creation, coal is exclusively excluded from the negative list of Taxable Goods. As a commodity that is mainly sold abroad, this can place coal entrepreneurs in a VAT Overpayment condition, considering that coal exports become VAT payable at a rate of 0% and the Input Tax can be credited. The methodology used in this research is literature study through secondary data analysis with a qualitative descriptive approach. The purposes of this study are to determine the consequences of the imposition of VAT on coal and estimate the potential of an increase or decrease in state revenues as a consequence of the imposition of VAT on coal. The results of this study indicate that the imposition of VAT on coal as regulated in Job Creation Law has an effect on increasing the potential for restitution to be claimed by taxpayers due to overpayments that occur. This is undoubtedly able to affect the performance of Indonesia’s economy nationally.